Підвищення стійкості газонних покриттів за різних умов зволоження - Rositska, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
The results of investigation analcime, tripoli, ammonium nitrate and salicylic acid influences on lipid peroxidation product and proline accumulation were shown. The dependence between the content of lipid peroxidation products, proline and photosynthetic pigments and soil moisture degree was established. Analcime, tripoli, ammonium nitrate and salicylic acid making had positive effect on ground and underground growth rates of plants and promoted adaptive potential to low water supply.